Model development based on small-sided games for the national football development program in Malaysia - Zulakbal Abd Karim; Thariq Khan Azizuddin Khan; Norhazira Abdul Rahim; Muhammad Muqri Aiman; Rajkumar Krishnan Vasanthi; Ali Nadzalan; Amin Akbar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The National Football Development Programme (NFDP) in Malaysia is a comprehensive initiative designed to improve the quality of football through structured coaching and player development, particularly focusing on youth engagement.